2009
DOI: 10.5021/ad.2009.21.2.164
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Esophageal Adenocarcinoma Metastasized to the Scalp

Abstract: Cutaneous metastases from internal malignancies are, occurring in 0.5% to 9% of cases. Lung, breast, and colorectal cancers are common primary tumors that metastasize to the skin; cutaneous metastasis usually occurs on the chest wall and abdomen as asymptomatic nodular patterns. Esophageal cancer is not nearly as common as breast, lung, and colorectal cancers, and esophageal cancer rarely metastasizes to the skin. Cutaneous metastasis of esophageal cancer is rare and metastasis to the scalp is extremely rare. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…2,14 According to literature, the average time of occurrence of the metastatic disease was estimated to be approximately 2.9 years after the onset of the primary tumor. 1 Esophageal adenocarcinoma may metastasize to various tissues of the human body. Most frequently esophageal adenocarcinoma metastasizes to the liver, lungs, and brain.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2,14 According to literature, the average time of occurrence of the metastatic disease was estimated to be approximately 2.9 years after the onset of the primary tumor. 1 Esophageal adenocarcinoma may metastasize to various tissues of the human body. Most frequently esophageal adenocarcinoma metastasizes to the liver, lungs, and brain.…”
Section: Discussionmentioning
confidence: 99%
“…More precisely, most of the primary tumors that develop at or near the gastroesophageal junction arise from Barrett's esophagus, as a complication of chronic gastroesophageal reflux disease. 1,14 Although in Western countries, the squamous cell carcinoma used to be the most common type of cancer, nowadays it is the adenocarcinoma that appears to be the most frequent one. 16 Histopathologic report of the biopsies obtained from the esophagus should be taken under consideration as it has been observed that the tumor subtype is a strongly connected to the survival rate factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations